2017
DOI: 10.29081/gsjesh.2017.18.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Fitness of 17-Year-Old Soccer Players Throughout the Annual Training Cycle According to Their Playing Position

Abstract: The purpose of the study was to assess the level of aerobic fitness in U17 Slovak elite soccer players throughout the annual training cycle according to their playing position. The participants were 14 soccer players who played for the 1st league U17 soccer team. To assess their levels of aerobic fitness, players performed the Yo-Yo intermittent recovery test Level 1 (Yo-Yo IRTL1) during four different phases of the annual training cycle. The results showed that the greatest distance covered by a player was 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…The values showed discrepancies in terms of quality (Velocity Bands 5-6) and quantity (TD) according to the different age groups, which can be explained in different ways despite the correlations with respect to the speed zones. The soccer-specific YYIR1 endurance test showed regular improvement in the case of the different age groups, similarly to the international analytical test results of Bangsbo et al (2008) and the test results of Ružbarský et al (2017) involving Slovakian elite U17 soccer players. One possible explanation could be the different skill levels of the different age groups (Tierney et al, 2016), while the different management styles and attitudes to the game on the part of the coaches who work with the different age groups might influence the performance and training session variables.…”
Section: Discussionsupporting
confidence: 84%
“…The values showed discrepancies in terms of quality (Velocity Bands 5-6) and quantity (TD) according to the different age groups, which can be explained in different ways despite the correlations with respect to the speed zones. The soccer-specific YYIR1 endurance test showed regular improvement in the case of the different age groups, similarly to the international analytical test results of Bangsbo et al (2008) and the test results of Ružbarský et al (2017) involving Slovakian elite U17 soccer players. One possible explanation could be the different skill levels of the different age groups (Tierney et al, 2016), while the different management styles and attitudes to the game on the part of the coaches who work with the different age groups might influence the performance and training session variables.…”
Section: Discussionsupporting
confidence: 84%
“…The values showed discrepancies in terms of quality (Velocity Bands 5-6) and quantity (TD) according to the different age groups, which can be explained in different ways despite the correlations with respect to the speed zones. The soccer-specific YYIR1 endurance test showed regular improvement in the case of the different age groups, similarly to the international analytical test results of Bangsbo et al [22] and the test results of Ružbarský et al [23] involving Slovakian elite U17 soccer players. One possible explanation could be the different skill levels of the different age groups [11], while the different management styles and attitudes to the game on the part of the coaches who work with the different age groups might influence the performance and training session variables.…”
Section: Discussionsupporting
confidence: 82%
“…Ružbarský and his colleagues [23] recorded similar findings among Slovakian elite U17 soccer players. Boullosa and his colleagues [24] devised an 8-week coaching program for Spanish elite soccer players.…”
Section: Introductionmentioning
confidence: 61%
“…The absolute values of V ̇O2 max increased significantly by 8.1%. Moroščák et al (2013) observed changes during the pre-season period from 49.0 to 56.7 ml • kg -1 • min -1 (+15.7%) in 15-16-year-old players after completing a 9-week training. In their study, aerobic fitness remained at a relatively stable level up to the playoffs (55.5-57.5 ml • kg -1 • min -1 ).…”
Section: Discussionmentioning
confidence: 83%
“…When performed on a regular basis, off-ice testing can also serve as a controlling mechanism for the effectiveness of the training intervention. Typically, such testing can be implemented in order to monitor changes in performanceassociated parameters before and after pre-season conditioning (Kutáč et al, 2017) or after a specifically oriented training program (Szmatlan-Gabrys et al, 2006) but also over the course of a competitive season (Delisle-Houde et al, 2019) or even whole annual cycle (Moroščák et al, 2013).…”
Section: Introductionmentioning
confidence: 99%